2016
DOI: 10.11138/mltj/2016.6.1.116
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hamstring injury in professional soccer players by isokinetic measurements

Abstract: SummaryObjectives: previous studies investigating the ability of isokinetic strength ratios to predict hamstring injuries in soccer players have reported conflicting results. Hypothesis: to determine if isokinetic ratios are able to predict hamstring injury occurring during the season in professional soccer players. Study Design: case-control study; Level of evidence: 3. Methods: from 2001 to 2011, 350 isokinetic tests were performed in 136 professional soccer players at the beginning of the soccer season. Fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 29 publications
(28 reference statements)
0
56
0
Order By: Relevance
“…Conventional H:Q ratios range from 0.6 to 0.9 [14] with such ratios rising when testing at higher velocities [15]. Ratios below 0.8 have been reported to increase the likelihood of sustaining a hamstring injury [12]. Although not a statistically significant finding, 18 players, accounting for the 4% of the total number of participants, displayed H/Q ratios of less than 0.6.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Conventional H:Q ratios range from 0.6 to 0.9 [14] with such ratios rising when testing at higher velocities [15]. Ratios below 0.8 have been reported to increase the likelihood of sustaining a hamstring injury [12]. Although not a statistically significant finding, 18 players, accounting for the 4% of the total number of participants, displayed H/Q ratios of less than 0.6.…”
Section: Discussionmentioning
confidence: 77%
“…This was found to be the case at all isokinetic speeds except at 300 °/sec, suggesting that hamstring strength plays an important role in joint balance and stabilization [13]. Research demonstrated that the probability of sustaining a hamstring injury is high if the concentric H/Q ratio, tested isokinetically at 60 °/sec, is less than 0.8 [12]. Conventional H: Q ratios range from 0.6 to 0.9 [14] with those ratios increasing when testing at higher velocities [15,16].…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…During isokinetic tests the athlete cannot perform a functional movement specific to a futsal match, however, this objective test may be important to identify strength asymmetries, which can relate to muscle injury risk that are common in high-intensity team sports. 20,21,38,42 To date, studies that evaluated peak isokinetic knee torque in futsal players have assessed strength performance or fatigue, 43 but not bilateral asymmetries.…”
Section: Discussionmentioning
confidence: 99%